2019
DOI: 10.1111/trf.15577
|View full text |Cite
|
Sign up to set email alerts
|

Screening for iron deficiency in surgical patients based on noninvasive zinc protoporphyrin measurements

Abstract: BACKGROUNDApproximately every third surgical patient is anemic. The most common form, iron deficiency anemia, results from persisting iron‐deficient erythropoiesis (IDE). Zinc protoporphyrin (ZnPP) is a promising parameter for diagnosing IDE, hitherto requiring blood drawing and laboratory workup.STUDY DESIGN AND METHODSNoninvasive ZnPP (ZnPP‐NI) measurements are compared to ZnPP reference determination of the ZnPP/heme ratio by high‐performance liquid chromatography (ZnPP‐HPLC) and the analytical performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In the third study on 584 surgical patients, most of which had concomitant inflammation, the noninvasive ZnPP measurement was compared with other iron status markers (eg, ferritin, transferrin saturation, soluble transferrin receptor), and it could be shown that ZnPP was the best single marker to identify patients with iron deficiency erythropoiesis [67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third study on 584 surgical patients, most of which had concomitant inflammation, the noninvasive ZnPP measurement was compared with other iron status markers (eg, ferritin, transferrin saturation, soluble transferrin receptor), and it could be shown that ZnPP was the best single marker to identify patients with iron deficiency erythropoiesis [67].…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy and applicability of the noninvasive ZnPP measurement have been investigated in three clinical studies on women postpartum, infants and children and on elderly surgical patients [46, 66, 67].…”
Section: Methodsmentioning
confidence: 99%
“…Neben der Anämiediagnostik kann der Ret-Hb, ebenso wie das Hepcidin, auch zum Therapiemonitoring während einer Eisensubstitution genutzt werden 21 . Auch nichtinvasive Methoden zur Detektion eines Eisenmangels sind Gegenstand aktueller Forschung, wie die Messung des Zinkprotoporphyrins (ZnPP) 22 .…”
Section: Diagnostik Der Postoperativen Eisenmangelanämieunclassified
“…We used soluble transferrin receptor levels (sTfR) levels as a clinical marker of ID at baseline and over the follow-up, since this parameter is not influenced by inflammation. [24] The threshold of more than 28.1 nmol/L was used to define ID as it was validated in older adults. [25][26][27] sTfR levels were measured with Tina-quant Transferrin ver.2 Test on a cobas c 502 analyser (Roche) using an Immunoturbidimetric assay.…”
Section: Exposures: Id and Anemiamentioning
confidence: 99%